2017
DOI: 10.1016/j.jamda.2017.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Transitions From Skilled Nursing Facility to Home: The Relationship of Early Outpatient Care to Hospital Readmission

Abstract: Background Many adults are discharged to skilled nursing facilities (SNFs) prior to returning home from the hospital. Patient characteristics and factors that can help to prevent post-discharge adverse outcomes are poorly understood. Objective To identify whether early post SNF discharge care reduces likelihood of 30 day hospital readmissions. Design Secondary data analysis using the Electronic Medical Record, Medicare, Medicaid and the Minimum Data Set. Participants/Setting Older (age > 65), community d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
25
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 40 publications
(43 reference statements)
2
25
1
Order By: Relevance
“…In Medicare data, HHC classification includes skilled services from nurses, physical therapists, occupational therapists, and/or speech‐language pathologists. Regardless, we find benefit of HHC services in general after SNF discharge for HF patients, which appears consistent with aforementioned work examining HHC during the SNF‐to‐home transition in other patient populations and other research evaluating the utility of home‐based transitional care after HF hospital discharge, such as home nursing visits within randomized controlled trial settings and early intensive HHC combined with physician follow‐up within 7 days . On the other hand, another study demonstrated that patients discharged from HF hospitalization with HHC referral had a higher risk of 30‐day readmission; however, the authors acknowledge that this finding is likely explained by selection bias in that those receiving HHC are more likely to have more advanced illness .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In Medicare data, HHC classification includes skilled services from nurses, physical therapists, occupational therapists, and/or speech‐language pathologists. Regardless, we find benefit of HHC services in general after SNF discharge for HF patients, which appears consistent with aforementioned work examining HHC during the SNF‐to‐home transition in other patient populations and other research evaluating the utility of home‐based transitional care after HF hospital discharge, such as home nursing visits within randomized controlled trial settings and early intensive HHC combined with physician follow‐up within 7 days . On the other hand, another study demonstrated that patients discharged from HF hospitalization with HHC referral had a higher risk of 30‐day readmission; however, the authors acknowledge that this finding is likely explained by selection bias in that those receiving HHC are more likely to have more advanced illness .…”
Section: Discussionsupporting
confidence: 90%
“…Home healthcare (HHC) involves the provision of skilled services to patients for both acute and chronic care management and can be used as support both during the transition from hospital to home and from SNF to home. Early high‐intensity home care after HF hospitalization has previously been found to be associated with lower 30‐day readmissions, while prior work has demonstrated that HHC is associated with reduced rates of readmission during the SNF to home transition in a safety net cohort …”
mentioning
confidence: 96%
See 1 more Smart Citation
“…We focus on readmissions within 7 days because little is known about the large proportion readmitted by that timeframe and the outcome is potentially most affected by clinical factors that may be amenable to care transitions and HHC interventions. 5,6 Early post-acute care attention shown to significantly reduce readmission hazard among selected populations, 7 including 8 to 7 percentage point rehospitalization reductions among HHC heart failure and sepsis patients, 8,9 provides the opportunity for prompt medication reconciliation, early nursing surveillance, vital sign monitoring, antibiotic stewardship, wound care, patient education, care coordination, and early outpatient assessment.…”
mentioning
confidence: 99%
“…The successful transition to home also mandates the coordination of care with community agencies, such as visiting nursing/home care, and/or area agencies on aging (AAA)/aging services access points (ASAPs), as there is evidence that reduced thirty-day readmissions may be associated with a home health visit within a week of SNF discharge [7]. AAA/ASAPs are private, not-for-profit agencies that provide case management and implementation of service plans, and many SNFs have an established relationship with their most local AAA/ASAP for assistance in supporting the transition of more dependent patients back to the community.…”
mentioning
confidence: 99%